Are lone mothers responsive to policy changes? Evidence from a workfare reform in a generous welfare state - Magne Mogstad; Chiara Pronzato (Institute for the Study of Labor (IZA), 2009)
There is a heated debate in many European countries about a move towards a welfare system that increases the incentives for lone mothers to move off welfare and into work. We analyze the consequences of a major Norwegian workfare reform of the generous welfare system for lone mothers. Our difference-in-differences estimates show that the policy changes were successful in improving labor market attachment and increasing disposable income of new lone mothers. By contrast, the reform led to a substantial decrease in disposable income and a significant increase in poverty among persistent lone mothers, because a sizeable group was unable to offset the loss of out-of-work welfare benefits with gains in earnings. This suggests that the desired effects of the workfare reform were associated with the side-effects of income loss and increased poverty among a substantial number of lone mothers with insurmountable employment barriers. This finding stands in stark contrast to evidence from similar policy changes in Canada, the UK, and the US, and underscores that policymakers from other developed countries should be cautious when drawing lessons from the successful welfare reforms implemented in Anglo-Saxon countries.
urn:nbn:de:101:1-2009102695
Keywords: C23; I32; I38; J00; 330; Lone mothers; workfare reform; difference-in-differences; heterogeneity; earnings; labor force participation; poverty; disposable income; Alleinerziehende; Mütter; Familienpolitik; Aktivierende Sozialhilfe; Wirkungsanalyse; Norwegen